Մերձավոր և Միջին Արևելքի երկրներ և ժողովուրդներ, XIX - Խմբ.` Ն. Հովհաննիսյան («Զանգակ - 97»)
One of the modern religions-Bahai faith, was founded in Persia in 19-th century by one of the followers of Bab-Baha'u'llah.There are about 6.000.000 believers of this faith in different countries.
Keywords: Պատմություն; Մերձավոր Արևելք; Միջին Արևելք